2013
DOI: 10.1111/j.1728-4465.2013.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Data Regarding Use of the Lactational Amenorrhea Method

Abstract: This study assesses the quality of Demographic and Health Survey (DHS) data regarding self-reported current use of the lactational amenorrhea method (LAM). LAM is an important modern contraceptive method that, when practiced correctly, has a 98 percent effectiveness rate six-months postpartum. The objectives of this study are to examine the accuracy of self-reported LAM use, compared with the constructed correct-practice variable, and to explore differentials in accuracy measures by characteristics at the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 5 publications
1
32
1
2
Order By: Relevance
“…Research has shown that postpartum women misunderstand the return to fecundity [18,[26][27][28]. This is true even among self-reported LAM users: a recent analysis of DHS data showed that many did not adhere to all three criteria for LAM effectiveness at the time of the survey [29]. Nevertheless, when postpartum women are exposed to postpartum family planning messages during other visits to health facilities, such as during labor and delivery, they are more likely to adopt a modern method [30,31].…”
Section: Discussionmentioning
confidence: 95%
“…Research has shown that postpartum women misunderstand the return to fecundity [18,[26][27][28]. This is true even among self-reported LAM users: a recent analysis of DHS data showed that many did not adhere to all three criteria for LAM effectiveness at the time of the survey [29]. Nevertheless, when postpartum women are exposed to postpartum family planning messages during other visits to health facilities, such as during labor and delivery, they are more likely to adopt a modern method [30,31].…”
Section: Discussionmentioning
confidence: 95%
“…O uso correto da LAM só é possível quando se associa o conhecimento com a confiança no MAC; ambas as orientações são de responsabilidade do profissional de saúde. Uma pesquisa realizada em 45 países entre 1998 e 2011 com o objetivo de analisar o uso correto desse método contraceptivo revelou que somente 26% dos usuários que usam a LAM cumprem os critérios para a prática correta (18).…”
Section: Discussionunclassified
“…Since 1989, lactational amenorrhea in the first six months postpartum when accompanied by exclusive and full or nearly full breastfeeding has been considered as a modern method of contraception (i.e., the lactational amenorrhea method, or LAM) (Kennedy, Rivera, and McNeilly 1989). 2 While few postpartum women in low-income countries report using LAM, many in fact meet the three criteria (menses has not returned, infant is less than six months old, and exclusive and full or nearly full breastfeeding) (Fabic and Choi 2013) and thus are de facto LAM users and largely protected from a pregnancy for six months.…”
Section: Reassessing Unmet Need For Family Planning In the Postpartummentioning
confidence: 99%